Three-Dimensional Design of Axial Flow Compressor Blades Using the Ball-Spine Algorithm - Ali Madadi; M.J Kermani; M. Nili-Ahmadabadi (Journal of Applied Fluid Mechanics, 2015)
Recently a new inverse design algorithm has been developed for the design of ducts, called ball-spine (BS). In the BS algorithm, the duct walls are considered as a set of virtual balls that can freely move along some specified directions, called ‘spines’. Initial geometry is guessed and the flow field is analyzed by a flow solver. Comparing the computed pressure distribution (CPD) with the target pressure distribution (TPD), new balls positions for the modified geometry are determined. This procedure is repeated until the target pressure is achieved. In the present work, the ball-spine algorithm is applied to three-dimensional design of axial compressor blades. The design procedure is tested on blades based on NACA65-410 and NACA65-610 profiles and the accuracy of the method is shown to be very good. As an application, the pressure distribution of the blade with NACA65-610 profiles is modified and the pressure gradient in the aft part of the blade is decreased and selected as target pressure distribution. The corresponding geometry which satisfies the target pressure is determined using the BS design algorithm.